Tubal Polyp Causing Postmenopausal Bleeding: Case Report - Çağlar, Gamze; Öztaş, Efser; Dinçer Cengiz, Sevim (Gynecology Obstetrics & Reproductive Medicine, 2011)
This is the first case of tubal polyp detected at the age of menapouase causing postmenapousal bleeding. The only finding was thickened endometrium at transvaginal ultrasonography. After hysteroscopic polypectomy, the endometrial thickness were within normal range for menapouse and at the follow-up the bleeding did not recur. Hysteroscopic polypectomy lead to subjective improvement in symptoms of bleeding and high satisfaction rates in this case. In postmenopausal persistent vaginal bleeding and increased endometrial thickness, intramural tubal polyps might be kept in mind in differential diagnosis. In such a situation hysteroscopy seems to be a simple method both for diagnosis and treatment instead of repetetive endometrial biopsies.